Identitas Kebalian; Rekonstruksi Etnik Bali Dalam Mempertahankan Identitas Pasca Konflik - Bagaskara, Arya; Hakiki, Kiki Muhamad; Rohmatika, Ratu Vina; Badruzaman, Badruzaman; Putra, Andi Eka (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study analyzes the various efforts made by the Balinuraga people to transform conflictual conditions into harmony after the conflict that has resulted in the loss of the Balinuraga community's collective identity, and makes destructive to constructive. So far there has been no research that examines the efforts made by the Balinese ethnic to maintain their identity after the conflict. This research uses descriptive qualitative methods with anthropological and sociological approaches by collecting data through interviews, observation and documentation. In the case analysis process, the writer uses several theories, namely ethnic identity theory, conflict transformation theory, adaptation theory, social integration theory and social interaction theory. The results showed that conflict was triggered by juvenile delinquency, expanded with the issue of ethnicity and group arrogance as an accelerator and conflict transformation efforts were carried out in four dimensions, namely personal, relational, structural and cultural transformation in order to achieve sustainable peace and national security. The implementation of the ethnic reconstruction strategy carried out by the Balinuraga community is considered effective enough to restore ethnic identity which was initially quite worrying after the conflict with ethnic Lampung in Balinuraga village, in general, the 4 reconstruction strategies that the researcher put in this thesis have included most of those carried out by the community. The Balinuraga.